1998
DOI: 10.1016/s0065-230x(08)60741-1
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and Cancer in the Mammary Gland: Shedding Light on an Old Dichotomy

Abstract: In this brief review, the development of breast cancer is discussed from the vantage of phenotypic differentiation, similar to what has been considered over the years for leukemias and melanomas, both of which express easily visible differentiation markers (Hart and Easty, 1991;Clarke et al., 1995;Lynch, 1995;Sachs, 1996;Sledge, 1996). The review is divided into a theoretical background for human breast differentiation and a discussion of recent experimental results in our laboratories with differentiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 116 publications
(146 reference statements)
1
43
0
1
Order By: Relevance
“…Considering that the p16-cyclin D.cdk4 pathway is usually non-functional in melanoma tumors, 16,34 and the lower cyclin D1 protein expression in non-proliferating melanocytes than in melanomas, 19,38 our data also suggests that use of melanocyte-specific promoters 39 preceding an antisense cyclin D1 sequence could provide the basis for a targeted retroviral vector potentially helpful against melanomas refractory to differentiation 25 and other traditional therapies.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Considering that the p16-cyclin D.cdk4 pathway is usually non-functional in melanoma tumors, 16,34 and the lower cyclin D1 protein expression in non-proliferating melanocytes than in melanomas, 19,38 our data also suggests that use of melanocyte-specific promoters 39 preceding an antisense cyclin D1 sequence could provide the basis for a targeted retroviral vector potentially helpful against melanomas refractory to differentiation 25 and other traditional therapies.…”
Section: Discussionmentioning
confidence: 71%
“…24 However, reversal of tumorigenicity by an antisense cyclin D1 cDNA, which activates the p53-p21WAF1 pathway and restores anti-oxidant activities, occurs without apparent cell death or concomitant increase in pigmentation or tyrosinase expression in K1735 melanoma cells, which are properties characteristic of melanocytic cell differentiation. 18 Our findings imply that in vivo and in vitro growth suppression of tumors refractory to differentiation 25 can occur independently of increased differentiation 20 and without cell death by induction of tumor growth retardation 26 mediated by an increase in p53 and superoxide dismutases.…”
Section: Introductionmentioning
confidence: 71%
“…A logical extension of this concept is that cancer cells can be induced to differentiate by suitable treatment to reactivate endogenous growth control mechanisms, which in a mutated and genetically damaged cancer cell context can culminate in apoptosis Leszczyniecka et al, 2001). This possibility has been addressed experimentally utilizing various model systems with the capacity to undergo in vitro differentiation (Lovat et al, 1997;Petersen et al, 1998;Wang and Chen, 2000;Leszczyniecka et al, 2001). Analysis of gene expression changes in differentiation therapy models provides a powerful experimental tool for delineating and understanding biochemical and molecular events mediating growth arrest of transformed cells Huang et al, 1999a, b;Jiang et al, 2000;Zhang et al, 2000).…”
mentioning
confidence: 99%
“…In addition, studies in such systems can lead to identification of specific molecules, which are important activators of the terminal differentiation process. Such molecules, in addition to being important analytical tools, also have therapeutic potential in anticancer gene therapy or drug design (Petersen et al, 1998;Zhang et al, 2000;Su et al, 2001;Fisher et al, 2003).…”
mentioning
confidence: 99%
“…5 The differentiation therapy has been successfully used in patients with blood-borne tumours and only a few number of studies have shown effectiveness in solid tumours. 6 Previously, uracil analogous, 7 new retinoid derivatives 3c or butyric acid prodrugs 5 have been described to induce differentiation.…”
Section: Introductionmentioning
confidence: 99%